2018
DOI: 10.1111/jpy.12811
|View full text |Cite
|
Sign up to set email alerts
|

Flip‐flop organization in the chloroplast genome of Capsosiphon fulvescens (Ulvophyceae, Chlorophyta)

Abstract: To better understand organelle genome evolution of the ulvophycean green alga Capsosiphon fulvescens, we sequenced and characterized its complete chloroplast genome. The circular chloroplast genome was 111,561 bp in length with 31.3% GC content that contained 108 genes including 77 protein‐coding genes, two copies of rRNA operons, and 27 tRNAs. In this analysis, we found the two types of isoform, called heteroplasmy, were likely caused by a flip‐flop organization. The flip‐flop mechanism may have caused struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Although our discovery of SVs represents the first clear report of CP heteroplasmy in siphonous green algae, recent Illumina-based studies of multiple genera reported numerous partial genomes [22] indicating that the phenomenon may be widespread in this group of algae. Heteroplasmy was recently documented in the related Ulvophycean order Ulothrichales in Capsosiphon fulvescens (C.Agardh) Setchell & N.L.Gardner [23], but occurs from the flipping of the short single copy section (SSC) found between the large inverted repeat characteristic of numerous green lineages [24]. This polymorphim differs from the SVs observed here that exhibit presence/absence of intronic ORFs.…”
Section: Discussionmentioning
confidence: 72%
“…Although our discovery of SVs represents the first clear report of CP heteroplasmy in siphonous green algae, recent Illumina-based studies of multiple genera reported numerous partial genomes [22] indicating that the phenomenon may be widespread in this group of algae. Heteroplasmy was recently documented in the related Ulvophycean order Ulothrichales in Capsosiphon fulvescens (C.Agardh) Setchell & N.L.Gardner [23], but occurs from the flipping of the short single copy section (SSC) found between the large inverted repeat characteristic of numerous green lineages [24]. This polymorphim differs from the SVs observed here that exhibit presence/absence of intronic ORFs.…”
Section: Discussionmentioning
confidence: 72%
“…, Kim et al. ) and intraspecific differences, aka heteroplasmy, have been found in Capsosiphon fulvescens , suggesting a possible major rearrangement between the two lineages of Nitzschia palea is possible.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable difference is the SSC regions which, occur in reverse orientation between the two strains. Rearrangements within algal lineages appear to be commonplace (Lemieux et al 2016, Kim et al 2018) and intraspecific differences, aka heteroplasmy, have been found in Capsosiphon fulvescens, suggesting a possible major rearrangement between the two lineages of Nitzschia palea is possible.…”
Section: Resultsmentioning
confidence: 99%
“…The chloroplast genome of V. pubescens was smaller than that of C. papaya, but its IR regions was longer than C. papaya. Unequal recombination and replication slippage can result in expansion and contraction of the IR regions, leading to variations in chloroplast genome size 59,63,64 . Five highly variable regions were identified in the V. pubescens and C. papaya chloroplast genomes, which are psbZ, trnG-GCC , trnH-GUG and psbA, trnS-GCU and trnG-UCC , and rps16.…”
Section: Discussionmentioning
confidence: 99%